FOREIGN POLICY OF NEW SOUTH AFRICA: REINSERTION AND REGIONAL AFFIRMATION - Rizzi, Kamilla Raquel; Schutz, Nathaly Xavier (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
South Africa is a country of singular importance for the understanding of contemporary International Relations. Situated at the Southernmost region of the African continent, coasted by the Indian and Atlantic oceans, South Africa occupies a geopolitical and geoeconomic strategic position. In the beginning of the 1990s, with the end of the Apartheid regime, the country starts a period of international reinsertion that presents as a fundamental feature the stabilization of the relations with the other African countries, especially its neighbors of Southern Africa. The objective of this article is to analyze the foreign policy of the New South Africa (from Nelson Mandela to Jacob Zuma), presenting as a central thread the role played by regional insertion for the South African ambitions in the international system.